OSELTAMIVIR IN PEDIATRIC PRACTICES (WORLD'S APPLICATION EXPERIENCE) - A.S. Kolbin; A.B. Ivanyuk; A.V. Kharchev (Union of pediatricians of Russia, 2008)
The authors analyzed the literature data on oseltamivir application for the flu prevention and treatment in pediatrics, which is most important for the practitioners. They showed peculiarities of the flu course in children, vulnerable groups, most often complications. Against this background, the application of etiotropic anti flu medications from the class of neuraminidase inhibitors becomes quite urgent. They showed that the etiotropic medications are the only group of medications now, which proved to be efficient against flu in children from the viewpoint of the evidentiary medicine. Oseltamivir is an efficient and safe medication for the prevention and treatment of type A and B flu among infants aged over 1, including h5n1 flu.Key words: oseltamivir, neuraminidase inhibitors, children.